THE SELF-ALIENATION AND DESTRUCTION OF IDENTITY: A POSTCOLONIAL STUDY OF TONI MORRISON'S BELOVED - Wahad Kalil Hashem (Journal of Learning on History and Social Sciences, 2024)
This article analyzes Toni Morrison's novel Beloved from the viewpoints. postcolonial perspective of Edward Said. By deconstructing the archetype of slavery, Morrison challenges white stereotypes of enslaved individuals and explores their feelings of self-alienation and identity deconstruction. This postcolonial analysis also situates the novel within the historical and political realities of African Americans in the United States. Sethe's character reveals the double oppression black women suffer and their contradictory experiences. In addition, the narrative structure and fragmented language of "Beloved" reflect the fractured experiences of enslaved African people, challenging traditional historical narratives dominated by white perspectives Morrison highlighted the intergenerational trauma caused by slavery and the ongoing systemic oppression and racism faced by African Americans. Analyzing the novel through Said's postcolonial lens also illuminates the intersectional constructions of power, culture, and identity and reveals the continuing impact of colonialism.